Blockchain Technology’s Impact on Port Logistic Operational Enhancement at Pontianak Port - Tigor Franky Devano Sianturi; Sundring Panca Djati; Marthaleina Ruminda; Librita Arifiani (Dinasti Publisher, 2024)
This study investigates the impact of blockchain technology on port logistics operations at Pontianak Port, West Kalimantan, Indonesia. Despite recent infrastructure developments, such as the Kijing Terminal, the port faces significant operational challenges, including inadequate traceability, incomplete real-time cargo information, and a lack of transparency. These issues lead to inefficiencies and mistrust among stakeholders, negatively impacting the port's reliability, operational effectiveness, and customer satisfaction. The research employs a structured quantitative design, surveying 110 participants involved in port operations, to examine the influence of traceability, transparency, and transaction efficiency on blockchain technology adoption and subsequent service quality improvements. Data analysis using SmartPLS 4.0 software confirms that enhanced traceability, transparency, and efficient transaction processes significantly impact the adoption of blockchain technology, which in turn significantly improves service quality. The study highlights the potential of blockchain to address these deficiencies and suggests future research to explore broader samples, additional influencing factors, and longitudinal studies.